Fat Body-Derived Juvenile Hormone Acid Methyltransferase Antagonizes Ecdysone by Inhibiting JNK-Dependent Autophagy in Drosophila melanogaster. - Liu, Z.H.; Xia, Y.; Zhai, Y.; Jiang, R.; Li, D.; Wang, H.L. (FASEB Journal (Federation of American Societies for Experimental Biology), 2026)
Juvenile hormone (JH), one of the main hormones in insects, is primarily synthesized in the corpora allata (CA). Studies have suggested tissues outside CA synthesize JH locally. Herein, we provide evidence that the Drosophila fat body serves as a novel extra-CA source of JH. Fat body-specific knockdown of JH acid methyltransferase (Jhamt), the rate-limiting enzyme in JH biosynthesis, significantly reduced JH titers locally and induced severe structural and functional defects, phenocopying CA ablation. These developmental defects were effectively rescued by dietary supplementation with JH analog, confirming that these defects arose from JH deficiency. Moreover, this hormone imbalance triggered ecdysone signaling-mediated autophagy, which contributed to Jhamt knockdown-induced defects. Mechanistically, we found JNK acts as a key downstream effector of JH and ecdysone to evoke autophagy. Further analysis revealed that JNK is antagonistically regulated by JH and ecdysone signaling. Collectively, our findings demonstrate that the fat body synthesizes JH locally to antagonize ecdysone signaling, with JNK serving as a critical integration node, thereby elucidating a novel tissue-specific axis for the coordination of insect development and metabolism.